Intensive Cultivation of Kiwifruit Alters the Detrital Foodweb and Accelerates Soil C and N Losses - Lago, María del Carmen F.; Gallego, Pedro P.; Briones, María J. I. (Frontiers in Microbiology, 2019)
The detrital food web plays an important role in the functioning of agro-ecosystems due to their positive effect on organic matter transformations and nutrient supply to the growing crops; however, the activities of the organisms involved are strongly influenced by agricultural practices. In NW Spain, commercial Hayward kiwifruit (Actinidia chinensis var. deliciosa) is intensively produced using conventional techniques (CONV); however, more sustainable methods, such as integrated (INT) and organic (ORG), have been increasingly adopted to decrease the negative impacts on the environment. We investigated the effects of these agricultural managements on earthworm abundance and functional diversity as well as microbial biomass and enzyme activity and evaluated the potential implications for nutrient retention and runoff in kiwifruit orchards. Our results showed that the CONV soils significantly contained fewer earthworms (ca. 80% less individuals than the INT and ORG systems), with their communities being mainly dominated by small epigeics, but a higher microbial biomass (0.53±0.06 mg C g-1 dw soil compared to <0.25 mg C g-1 dw soil in INT and ORG), and 20% more activity of the enzymes involved in C (-glucosidase) and N mineralization (urease). Consequently, more C and N was lost from these soils (on average, >37% more CO2, and five times more DIN) than from the less intensively managed soils. In contrast, the INT and ORG systems sustained a more complex and functionally diverse soil food web that lead to higher soil C and N retention. Therefore, agriculture management (i.e. intensive vs. less intensive) and its effects on the structure of the below-ground communities (i.e., microorganisms plus surface detritivores vs. deep burrowers plus geophagous forms) determine the nutrient sink/source function of these agro-ecosystems. These findings highlight the importance of including the contribution of soil biota to soil processes when optimizing fertilization loads and mitigating environmental impacts of agricultural practices